GEOCHEMISTRY OF THE GAS MANIFESTATIONS OF GREECE: METHANE AND LIGHT HYDROCARBONS - Daskalopoulou, K.; D’Alessandro, W.; Cabassi, J.; Calabrese, S.; Fiebig, J.; Grassa, F.; Kyriakopoulos, K.; Parello, F.; Tassi, F. (Bulletin of the Geological Society of Greece, 2016)
Greece has a very complex geodynamic setting deriving from a long and complicated geological history being characterized by intense seismic activity and enhanced geothermal gradient. This activity, with the contribution of an active volcanic arc, favours the existence of many gas manifestations. Depending on the prevailing gas species, the latter can be subdivided in three main groups: CO2-, N2- and CH4- dominated. In the present work, we focus on methane and light hydrocarbons (C2-C6) to define their origin. CH4 concentrations (<2 to 915,200 μmol/mol) and isotopic ratios (δ13C -79.8 to +16.9 ‰, δD -298 to +264‰) cover a wide range of values indicating different origins and/or secondary post-genetic processes. Samples from gas discharged along the Ionian coast and in northern Aegean Sea have a prevailing microbial origin. Cold and thermal gas manifestations of central and northern Greece display a prevalent thermogenic origin. Methane in gases released along the active volcanic arc is prevailingly abiogenic, although thermogenic contributions cannot be excluded. Gases collected in the geothermal areas of Sperchios basin and northern Euboea are likely affected by strong secondary oxidation processes, as suggested by their highly positive C and H isotopic values (up to +16.9‰ and +264‰ respectively) and low C1/(C2+C3) ratios.